2016
DOI: 10.1016/j.mrrev.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The cytokinesis-block micronucleus (CBMN) assay in human populations exposed to styrene: A systematic review and meta-analysis

Abstract: Styrene is a building-block of several compounds used in a wide array of materials and products. The most important human exposure to this substance occurs in industrial settings, especially among reinforced-plastics industry workers. The effect of occupational exposure to styrene on cytogenetics biomarkers has been previously reviewed with positive association observed for chromosomal aberrations, and inconclusive data for the micronucleus assay. Some limitations were noted in those studies, including inadequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Edible mushrooms are regarded as non-toxic and safe, but recent investigations reported that some of them cause DNA damages [27]. Numerous studies showed that the CBMN assay is a valid test for detection of genomic damage caused both in vitro [28,29] and in vivo [30,31]. Our results of CBMN assay showed that the extract was genotoxic in higher tested concentrations.…”
Section: Cytotoxic Activitymentioning
confidence: 54%
“…Edible mushrooms are regarded as non-toxic and safe, but recent investigations reported that some of them cause DNA damages [27]. Numerous studies showed that the CBMN assay is a valid test for detection of genomic damage caused both in vitro [28,29] and in vivo [30,31]. Our results of CBMN assay showed that the extract was genotoxic in higher tested concentrations.…”
Section: Cytotoxic Activitymentioning
confidence: 54%
“…A recent review and meta-analysis focused on the induction of MN in human subjects was published by Costa et al (2016). The authors concluded that overall there was an increase in MN among styrene-exposed workers and that the findings of an increase were consistent across studies even though the review reported significant heterogeneity in the meta-analysis of all studies.…”
Section: Cancer Mode Of Actionmentioning
confidence: 99%
“…Styrene is a solvent used extensively in the polymer-processing industry. It is a toxic compound which is known to have numerous adverse effects on human health ( 1 4 ). As a result of this toxicity, there is considerable interest in styrene waste management solutions, including the potential for microbial bioremediation.…”
Section: Genome Announcementmentioning
confidence: 99%